IMPROVEMENT OF SEISMOLOGICAL EARTH MODELS BY USING DATA WEIGHTING IN WAVEFORM INVERSION - Takeuchi N.; Kobayashi M. (My University, 2004)
We present a new method for data weighting in waveform inversion to improve the obtained seismological earth model. We define 'sensitivity' as an index to show the homogeneity of the waveform inversion data set. The sensitivity is directly evaluated from the partial derivatives of the synthetic seismograms and can be evaluated regardless of the method used to compute the synthetics. In this study we use the Direct Solution Method, which is a highly suitable method because of its accuracy and efficiency. If we weight the data so that the sensitivity is more or less homogeneous throughout the whole Earth, we can achieve homogeneous resolution for the entire region. The obtained model is an improvement over models obtained by previous inversion schemes, in the sense that the new model efficiently retrieves the robust information in the data. The inversion of a large data set using our methods can be expected to lead to further improvement of seismological earth models.
Keywords: DIRECT SOLUTION METHOD; EARTH'S INTERIOR; INVERSE PROBLEM; SYNTHETIC SEISMOGRAMS